Analyzing Expressive Speech Acts in Comments on ‘Teacher Welfare Issues in the National Education System Bill’ - Dini Artini Dini; Rika Ningsih Rika (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This research aims to explain and describe expressive speech acts in the comment section of the Ministry of Education and Culture’s YouTube account “Peel Through the Issue of Teacher Welfare in the Sisdiknas Bill”. The comment section contained seventy examples of expressive speaking activities which analyzed using qualitative approach. Results indicate the presence of 70 instances of expressive speech acts within the comment column, categorized as follows: expressions of gratitude (36), apologies (1), praise (16), complaints (5), and expressions of happiness or pleasure (12). The present study provides significant contributions to the understanding of the many forms and functions of expressive speech acts in virtual communication environments. Through the exploration of the diverse range of expressive speech acts observed inside the comment part of this renowned YouTube account, this study enhances our comprehension of contemporary communication dynamics. Moreover, the conducted research not only paves the way for future inquiries but also holds significant practical consequences for instructional practices in educational settings. Promoting digital literacy and effective communication skills in kids requires an understanding of how people express themselves in digital spaces. Educators have the opportunity to integrate these research findings into their instructional programs and facilitate debates regarding internet communication etiquette, thereby cultivating a generation that is more equipped with knowledge and skills in the digital realm. In summary, this study provides light on the nuances of expressive speech acts in digital contexts and establishes the groundwork for future research in this dynamic field of communication.